Characterization of a novel recombination event in the Deformed wing bee virus polymerase gene - GORAS, G; RUETHER, IGA; TANANAKI, CH; GOUNARI, S; LIOLIOS, V; KANELIS, D; ARGENA, N; RODOPOULOU, M; KARAZAFIRIS, EM; THRASYVOULOU, A (Journal of the Hellenic Veterinary Medical Society, 2018)
Honeybee populations are known to be infected by numerous viruses. Reverse transcription-PCR (RT-PCR) of regions of the RNA-dependent RNA polymerase is often used to diagnose the presence in apiaries and also to classify the type of virus detected. In this report, through analysis of the RdRp gene, we describe a novel recombination event in the DWV genome. Similarity plot analysis amplified from hundred positive individuals identified a previously undescribed recombination point in the 5’ region of the polymerase gene. To our knowledge this is the first description of recombination in the DWV polymerase gene and highlights the continuous genetic evolution of these viruses.